2006
DOI: 10.1016/j.cardiores.2006.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular adipose tissue promotes vasoconstriction: the role of superoxide anion

Abstract: These results show that PVAT enhances the arterial contractile response to perivascular nerve stimulation through the production of superoxide mediated by NAD(P)H oxidase, and that this enhancement involves activation of tyrosine kinase and MAPK/ERK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
0
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(193 citation statements)
references
References 47 publications
9
165
0
19
Order By: Relevance
“…3). These findings imply that the adventitia layer affects the contraction of media layer in epicardial coronary arteries in response to high K ϩ , which is consistent with previous experimental measurements in other vessels (5,6,26). The differences in the magnitude of active stress between circumferential and axial directions may be related to the microstructural properties of the intima-media and adventitia layers.…”
Section: Discussionsupporting
confidence: 91%
“…3). These findings imply that the adventitia layer affects the contraction of media layer in epicardial coronary arteries in response to high K ϩ , which is consistent with previous experimental measurements in other vessels (5,6,26). The differences in the magnitude of active stress between circumferential and axial directions may be related to the microstructural properties of the intima-media and adventitia layers.…”
Section: Discussionsupporting
confidence: 91%
“…Under our experimental conditions, this procontractile potency implicated O2·-generated by xanthine oxidase. This observation confirms and extends the findings by Gao, et al [23] who showed that, in response to peripheral nerve activation by electrical field stimulation, PVAT enhances arterial contractility through the production of O2·-mediated by NADPH oxidase. In this context our findings clearly demonstrate that in HFD rats the procontractile activity of PVAT decreased.…”
Section: Hfd Reduces Pvat Procontractile Activitysupporting
confidence: 92%
“…Adventitial fibroblasts possess Nox2 and Nox4 and perivascular adipose tissue expresses Nox4. 102,103 Nox regulation Regulation of Noxes is complex and involves many NADPH oxidase subunits and multiple signaling pathways. All Noxes, except Nox5, seem to have an obligatory need for p22phox.…”
Section: Vascular Generation Of Rosmentioning
confidence: 99%